"To Clean or Not to Clean?" Reducing Daily Routine Hotel Room Cleaning by Letting Tourists Answer This Question for Themselves. (January 2021) - Knezevic Cvelbar, Ljubica; Grün, Bettina; Dolnicar, Sara
Changing default settings has proven to be a powerful approach to influencing consumer decisions without denying consumers the possibility of choosing freely. This is only the second study investigating the effectiveness of defaults in tourism, and the first testing also the combined effect of default changes and pro-environmental appeals in the context of changing room cleaning defaults in hotels from automatic daily cleaning (with the choice of opting out) to no daily routine cleaning (with the choice of opt-in and requesting a free room clean every day). Results from a quasi-experimental study conducted in a three-star city hotel suggest that the change in defaults significantly reduced room cleaning, with only 32% of room cleans requested on average. Adding a pro-environmental appeal to the change in defaults did not further reduce room cleaning overall, but has an effect on certain segments of hotel guests.